Development and psychometric properties of a belief-based Physical Activity Questionnaire for Diabetic Patients (PAQ-DP) - Ghazanfari, Zeinab (BioMed Central, 2010)
BACKGROUND: This study carried out to develop a scale for assessing diabetic patients' perceptions about physical activity and to test its psychometric properties (The Physical Activity Questionnaire for Diabetic Patients-PAQ-DP). METHODS: An item pool extracted from the Theory of Planned Behavior literature was generated. Then an expert panel evaluated the items by assessing content validity index and content validity ratio. Consequently exploratory factor analysis (EFA) was performed to indicate the scale constructs. In addition reliability analyses including internal consistency and test-retest analysis were carried out. RESULTS: In all a sample of 127 women with diabetes participated in the study. Twenty-two items were initially extracted from the literature. A six-factor solution (containing 19 items) emerged as a result of an exploratory factor analysis namely: instrumental attitude, subjective norm, perceived behavioral control, affective attitude, self-identity, and intention explaining 60.30% of the variance observed. Additional analyses indicated satisfactory results for internal consistency (Cronbach's alpha ranging from 0.54 to 0.8) and intraclass correlation coefficients (ranging from 0.40 to 0.92). CONCLUSIONS: The Physical Activity Questionnaire for Diabetic Patients (PAQ-DP) is the first instrument that applies the Theory of Planned Behavior in its constructs. The findings indicated that the PAQ-DP is a reliable and valid measure for assessing physical activity perceptions and now is available and can be used in future studies.